Enlightenment hospitality - Still, J (Voltaire Foundation, 2017)
Hospitality, in particular hospitality to strangers, was promoted in the eighteenth century as a universal human virtue, but writing of the period reveals many telling examples of its abuse. Through analysis of encounters across cultural and sexual divides, Judith Still revisits the current debate about the social, moral and political values of the Enlightenment. Focussing on (in)hospitality in relation to two kinds of exotic Other, Judith Still examines representations of indigenous peoples of the New World, both as hosts and as cannibals, and of the Moslem ‘Oriental’ in Persia and Turkey, associated with both the caravanserai (where travellers rest) and the harem. She also explores very different examples of Europeans as hosts and the practice of ‘adoption’, particularly that of young girls. The position of women in hospitality, hitherto neglected in favour of questions of cultural difference, is central to these analyses, and Still considers the work of women writers alongside more canonical male-authored texts. In this thought-provoking study, Judith Still uncovers how the Enlightenment rhetoric of openness and hospitality is compromised by self-interest; the questions it raises about attitudes to difference and freedom are equally relevant today. 1. Introducing Enlightenment hospitality 2. The New World: received as gods 3. The New World: eating the other 4. Enlightenment Persia 5. Turkish travels: hospitable harems and good guests 6. The other as guest: the special case of adoption and sexual predation 7. Revolution and rights Concluding questions: now and then Bibliography Index